2006
DOI: 10.1021/la0607050
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Linear-Dendritic Triblock Copolymers Composed of Poly(amidoamine) and Poly(propylene oxide) and Their Micellar-Phase and Encapsulation Properties

Abstract: A novel amphiphilic ABA dendritic-linear-dendritic block copolymer consisting of poly(amidoamine) and poly(propylene oxide) has been synthesized. The solution-phase behavior of the block copolymer was studied as a function of the generation of the dendritic block, ionic strength, and solution pH. The triblock self-assembles in aqueous media to form stable micelles with CMC values ranging from 10(-6) to 10(-5) M. Dynamic light scattering results indicate the formation of particles ranging from 9 to 18 nm in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 49 publications
(60 reference statements)
3
101
0
Order By: Relevance
“…All of the micelles have core-shell structures with water-insoluble blocks forming cores and watersoluble blocks acting as coronas. One promising application of this type of aggregates is for drug delivery [1][2][3][4][5][6][7][8][9]. Usually, hydrophobic drugs can be loaded in the cores of the micelles to lower its toxicity in human body, and to prolong their circulation time in blood [10].…”
Section: Introductionmentioning
confidence: 99%
“…All of the micelles have core-shell structures with water-insoluble blocks forming cores and watersoluble blocks acting as coronas. One promising application of this type of aggregates is for drug delivery [1][2][3][4][5][6][7][8][9]. Usually, hydrophobic drugs can be loaded in the cores of the micelles to lower its toxicity in human body, and to prolong their circulation time in blood [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the grafted PEG chains enhance the affinity of aggregates in THF. In the earlier reports, the mid-generation dendrimers usually create a significantly deformed morphology when self-assembly driven by hydrophilic and hydrophobic interactions [21,22]. In our case, due to the flexibility of peripheral PEG arms, the rigid h-PAMAM units can be mainly directed toward one side in the block-selective solvent, eventually leading to formation of the spherical micelles with an h-PAMAM core and grafted PEG chains.…”
Section: Resultsmentioning
confidence: 54%
“…[15][16][17][18] For example, it has been shown that critical micelle concentration (CMC) of linear-dendritic copolymers decreases with increasing generation in keeping with increasing hyrophobicity of the dendrons. [ 19,20 ] Morphology of an azo-dendron-poly(ethylene glycol) (PEG) polymer changed from nanofi bers to micelles to vesicles with increasing dendron generations. [ 21 ] However, hydrophobicity or hydrophilicity of these copolymers increases rapidly with generation of dendron because of exponential increase in the number of terminal groups and concomitant increase in dendron size.…”
Section: Introductionmentioning
confidence: 99%